Analisis Keterampilan Berpikir Kritis Siswa SD Kreatif Rusyda Kelas VI dalam Menjawab Soal Energi dan Perubahannya - Dira Supratiwi; Suyit Ratno; Dwi Rahmi A Tanjung; Aurora Febriani Br Barus; Haya Sabila Aulia; Nesa Andari; Sekar Melati Pasaribu; Inpresdo Wessly Sinaga (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Energy is the ability to do or change something. It can be found in various forms in everyday life, such as electrical energy flowing through cables, thermal energy produced by stoves, or kinetic energy generated by vehicles. Energy can also come from natural sources, such as the sun, wind, and water. This research aims to enhance students' ability to think critically in understanding the material on energy and its changes. This research uses a quantitative method; data were collected from 27 students through 10 questions discussing the concept of energy. Effective education not only helps students better understand what they are doing, but also prepares them to face environmental issues in the future. In addition, innovative learning methods such as project-based learning should be incorporated into the curriculum to build critical thinking skills. Therefore, it is expected that this research will help improve the energy education curriculum in elementary schools and encourage students to participate more actively in sustainability issues.